Formulation of Millet Milk and Herb Extract Enriched Yogurt and to Assess Its Nutritional Characteristics: Life Sciences-Nutrition and Dietetics - S. Nair, Sandra.; Peerkhan, Nazni (International Journal of Life Science and Pharma Research, 2022)
The dairy-based probiotic products dominate the functional food market primarily yogurts. Fibers derived from byproducts of the fruit processing sector, herb extracts, and fresh spices have all been introduced to the milk and yogurt product portfolio. The main objective of this study was to investigate to what extent the addition of barnyard millet milk and different herb oleoresins in yogurts will improve its qualitative properties and antioxidant activity. The cow’s milk, barnyard millet milk, and the oleoresins obtained from three other herbal plants are considered in this study, respectively, Sage (Salvia Officinalis L.), Oregano (Origanum Vulgare L.) and Rosemary (Rosmarinus Officinalis). On day1, day 14 and day 28 after yogurt preparation, the effect of millet milk and oleoresins prepared from different herbs (0.5, 1, 1.5 percent) on yogurt qualitative features (pH, titratable acidity, syneresis, color parameters, viscosity total polyphenol and flavonoid and antioxidant activity) was evaluated. The final results demonstrated that after 28 days of storage, the physicochemical parameters of the yogurt with millet milk and herb oleoresins were improved over CM samples. As the proportion of herb extract increased, so did the total polyphenol and flavonoid values. Yogurt containing herb extract exhibited antioxidant activity that was notably higher than the standard and improved proportionately as herb extract concentration increased. When Oregano (Origanum Vulgare L.) oleoresin and barnyard millet milk were combined, the best antioxidant capability was obtained. As per the results, the apparent viscosity of the CM yogurt was higher than that of enriched yogurt samples, while the model with 0.5 percent Oregano (Origanum Vulgare L.) oleoresin addition seemed to have the best nutritional value. The findings of this study lead to the conclusion that yogurts enriched with barnyard millet milk and natural extracts could be used as functional foods with significant health benefits.